Purely-elastic flow instabilities in a 3D six arms cross-slot geometry - A. Afonso (2008)
A numerical study of the creeping flow of an UCM fluid is carried out in a three-dimensional cross-slot geometry with inlets and outlets in all three orthogonal directions. Using two different inlet flow rate configurations, I-o = 4:2 and 2:4, representing uniaxial extension and biaxial extension, respectively, it was possible to assess the importance of different types of extensional flow near the stagnation point. Two different methods of calculation of the polymer stress were used, the standard approach and the log-conformation approach. The uniaxial extension flow configuration is prone to the onset of steady flow asymmetries, at a rather small Deborah number (De(crit) = 0.21) and regardless of the stress computation method. However, for the biaxial extension flow configuration a perfectly symmetric flow has so far been observed up to De = 0.5 using the log-conformation approach. The use of these two configurations allowed the variation of the amount of stretch and compression near the stagnation point, providing new insights into the viscoelastic flow instability mechanisms in cross-slot flows.